ASSESSING THE SELF-PERCEIVED USE OF READING STRATEGIES IN ESL READING COMPREHENSION: A NEEDS ANALYSIS - Ting Pick Dew; Suyansah Swanto; Wardatul Akmam Din; Kamsilawati Kamlum (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Despite great appreciation on the important roles played by metacognitive reading strategies in the attainment of comprehension, heightened prevalence of reading difficulties is depicted among Malaysian learners. Therefore, this study aimed at investigating the current status of self-perceived use of metacognitive reading strategies among the ESL learners in six secondary schools in one of the districts in Sabah. Utilizing an adapted version of Revised Metacognitive Awareness of Reading Strategy Inventory (MARSI-R), data was obtained from 274 ESL learners in the same district. Descriptive analysis was used to determine the mean scores of three sub reading strategies, namely global reading strategies, problem-solving strategies and support strategies. The findings revealed that despite being aware of the use of metacognitive reading strategies, little emphasis was given on optimizing the use of global reading and support strategies, resulting in only medium usage of these two strategies. Therefore, it may be concluded that the findings implied the need to develop a reading comprehension module that incorporates the use of metacognitive reading strategies within reading comprehension instruction to facilitate Malaysian ESL learners to improve their reading comprehension.